KINERJA PELAYANAN PUBLIK KEPADA KONSUMEN DI KANTOR PT.PLN (PERSERO) WILAYAH KECAMATAN KEMBAYAN KABUPATEN SANGGAU - Henita E.01108019 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem that faced by the PT. PLN (Persero) in Kembayan District Sanggau Regency were the complaint for the electricity such as the cost of the electricity, the problem in typing the bill, an error reading meters , home interference ( installation ), electricity extinguishing and other damages, therefore it gives the bad effect for the performance of publik service. So that, the writer conducted this research with the title ” the publik service performance for the consumers at PT PLN (Persero) in Kembayan District Sanggau Regency”. The performance of the PT. PLN (Persero) in Kembayan District Sanggau Regency in giving the  publik services was measured from four aspects, there are : Productivity, Responsiveness, Responsibility, and Accountability. This research method was used descriptive qualitative research.The steps in conducted this research was through the library research and field research. The result of this research were the service was good enough, in solve the complaints PLN have tried to help the customer to deliver their complaints, employee skills are good enough, and employee behavior is good enough in serve consumers but the services of  PLN are still lacking because some consumers feel not satisfied, the inability of generators be a cause of electricity extinguishing  and be the lack of PLN in give the service. The Suggestions in this research was the performance of publik services should be more improved with more attention to the needs and responsiveness, improving service are still considered  less and doing the work wholeheartedly so that consumers are satisfied with the performance of publik service that has been given. Keywords: Performance, Service, Productivity, Responsiveness, Responsibility and Accountability.